Why Does Academic Enjoyment Affect Foreign Language Proficiency? The Mediating Role of Elaboration Strategies - Yajun Wu; Xia Kang (ELE Reviews: English Language Education Reviews, 2023)
From the perspective of positive psychology, academic enjoyment, a positive achievement emotion, positively impacts school outcomes. However, studies have yet to explore the mediating mechanism between academic enjoyment and achievement. This research investigated the direct and indirect effects of academic enjoyment on foreign language (FL) proficiency. Specifically, this study endeavored to test the role of FL enjoyment on FL elaboration strategies and whether FL elaboration strategies, in turn, affects FL proficiency. Data were collected from 505 Chinese secondary school students aged 12 to 15 using convenience sampling. Structural equation modeling (SEM) and mediation analyses found that FL elaboration strategies partially mediated the relationship between FL enjoyment and FL proficiency. Implications, shortcomings, and directions for further studies are also discussed.